Pembinaan Akuntansi Dan Pelaporan Keuangan Pada Sekolah Menengah Kejuruan (SMK) Batam Business School - Syahril Effendi; Tukino Tukino; Baru Harahap (LPPM Universitas Putera Batam, 2022)
Vocational schools that are located close to each other, but have not synergized in the utilization of existing resources in each school are seen as less efficient. On the other hand, several SMKs have adequate resources and potential to expand and at the same time improve educational services to the community through various education and training programs. In connection with these conditions, the Directorate of Vocational High Schools has programmed to combine these schools in one management and increase the capacity of Vocational High Schools through various education and training programs under the name of Greater Vocational High School Development. Financial statements function as a tool to analyze financial performance that can provide information about financial position, business, performance and cash flow so that it can be used as a basis for making economic decisions. The object of this service is aimed at the Batam Business School Vocational High School (SMK) around the Sekaran Village where the majority of Batam Business School Vocational High School (SMK) players do not have financial reports